The Status of Translated Literature in the Creation of Hebrew Literature in Pre-State Israel (the Yishuv Period) - Shavit, Zohar (Meta)

(untitled) (Les Presses de l'Université de Montréal, 1998)
AbstractThis article discusses the central function translated litterature had in the crystallization of original Hebrew culture. It looks at how translated literature was used to fill some of the missing functions of original literature and how the activity of translation was perceived as a form of literary creation. It analyses the process according to which the attitude towards translational activity changed from a favorite one (regarding it as an essential condition for the creation of a literary center), to a hostile one which saw it as a rival to original literature and Hebrew culture. When the literary system began to be self-sufficient, translated literature was no longer required to serve a "stop-gap" as it was the case in the early years of the establishment of a literary center in Eretz-Israel. The debate about the desired relationship between original and translated literature continued all the same to be one of the fundamental issues facing those responsible for determining editorial policy, showing decreasing tolerance for the status of translated literature and demanding an "improvement" in the status of original writing, together with calls to allocate fewer resources to translation.